2022
DOI: 10.4102/phcfm.v14i1.3301
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors of chronic malnutrition amongst children under five in Eswatini

Abstract: Background: About 20 million children under fi-ve in Southern Africa have chronic malnutrition. This study determines the prevalence of chronic malnutrition and associated risk factors amongst children under five.Aim: To determine the proportion of children with chronic malnutrition and investigate associated risk factors of chronic malnutrition.Setting: The study was conducted in communities in the four regions of Eswatini.Methods: This study is a retrospective cross-sectional study that used data from a Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…8 The literature confirmed that malnutrition is a critical public health problem in children under five years and requires concerted efforts and multisectoral response. 9 The findings highlight that various factors such as demographic status, social and economic status and governments' priorities in addressing food insecurity are key attributes to the status of malnutrition in Southern Africa.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…8 The literature confirmed that malnutrition is a critical public health problem in children under five years and requires concerted efforts and multisectoral response. 9 The findings highlight that various factors such as demographic status, social and economic status and governments' priorities in addressing food insecurity are key attributes to the status of malnutrition in Southern Africa.…”
Section: Introductionmentioning
confidence: 95%
“…A qualitative systematic review brings together research on a topic, systematically searching for research evidence from primary qualitative studies and drawing the findings together. 9 The PICO (Population, intervention, comparison, outcome, settings) framework to develop the search strategy was used to search for literature related to Shipanga V et al Int J Community Med Public Health. 2024 Jan;11(1):363-370 the topic with a research question "What is the state of knowledge on malnutrition for children under 5 years?…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…https://www.hsag.co.za Open Access Dlamini and Tlou (2022) conducted a study on prevalence and associated risk factors of chronic malnutrition among children under 5 years in Eswatini. The findings revealed that a large number of children under the age of 5 years still fail to achieve their growth potential, as reflected by the prevalence of malnutrition.…”
Section: Introductionmentioning
confidence: 99%